2013
DOI: 10.5753/jis.2013.623
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Interactive Systems based on Brain-Computer Interfaces

Abstract: Brain-Computer Interface (BCI) enables users to interact with a computer only through their brain biological signals, without the need to use muscles. BCI is an emerging research area but it is still relatively immature. However, it is important to reflect on the different aspects of the Human-Computer Interaction (HCI) area related to BCIs, considering that BCIs will be part of interactive systems in the near future. BCIs most attend not only to handicapped users, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
2
3
0
1
Order By: Relevance
“…This opinion is rather qualified in the scientific community, which reported that BCIs suffer from (1) a low transfer rate, (2) a lack of market-ready, affordable, and user-friendly research-grade EEG acquisition devices, and (3) a gap between the game design and graphics of video games available on the market vs. in laboratories. Priorities of these limitations for video game development are discussed in the literature (Nijholt et al, 2009;Ferreira et al, 2013;Marshall et al, 2013;van de Laar et al, 2013;Ahn et al, 2014;Cattan et al, 2018b;Kerous et al, 2018;Vasiljevic and Miranda, 2019;Pierce et al, 2020), and in general preponderance of quantitative over qualitative aspects is criticized (Nijholt et al, 2009;Vasiljevic and Miranda, 2019). This article supports the claim that BCIs are not ready for general public use, based on other aspects than performance.…”
Section: Introductionsupporting
confidence: 60%
“…This opinion is rather qualified in the scientific community, which reported that BCIs suffer from (1) a low transfer rate, (2) a lack of market-ready, affordable, and user-friendly research-grade EEG acquisition devices, and (3) a gap between the game design and graphics of video games available on the market vs. in laboratories. Priorities of these limitations for video game development are discussed in the literature (Nijholt et al, 2009;Ferreira et al, 2013;Marshall et al, 2013;van de Laar et al, 2013;Ahn et al, 2014;Cattan et al, 2018b;Kerous et al, 2018;Vasiljevic and Miranda, 2019;Pierce et al, 2020), and in general preponderance of quantitative over qualitative aspects is criticized (Nijholt et al, 2009;Vasiljevic and Miranda, 2019). This article supports the claim that BCIs are not ready for general public use, based on other aspects than performance.…”
Section: Introductionsupporting
confidence: 60%
“…The wired model is a standard system, whereas the wireless model is an evolving solution. Many companies have designed portable headsets to provide greater comfort at a low cost [ 272 ].…”
Section: Resultsmentioning
confidence: 99%
“…The wired model is a standard system, whereas the wireless model is an evolving solution. Many companies have designed portable headsets to provide greater comfort at a low cost [272]. Table 2 summarizes the companies and their equipment, which were used in specific research areas.…”
Section: Rq2: What Are the Most Common Types (Wired Or Wireless) Of Noninvasive Eeg-based Bci Equipment That Have Been Used In Brain Studmentioning
confidence: 99%
“…As aplicações tradicionais de BCIs se concentram em solucões que promovam a interação entre humanos e máquinas atravĂ©s de sinais cerebrais (Ferreira et al, 2013), e.g., controle de dispositivos mecânicos, como uma cadeira de rodas, mas sem a necessidade de força manual. As aplicações sĂŁo diferenciadas de acordo com aspectos como: (i) dispositivo empregado (invasivo/nĂŁo-invasivo); (ii) estĂ­mulo do sinal (exĂłgeno/endĂłgeno); (iii) forma de processamento (sĂ­ncrona/assĂ­ncrona); e (iv) objetivo (ativo, passivo ou reativo) (Vasiljevic and Miranda, 2020).…”
Section: Interface CĂ©rebro-computadorunclassified